Project Review: Arun III Hydroelectric Project - Pyakurel, Keshab (Hydro Nepal: Journal of Water, Energy and Environment, 2015)
Not Available. HYDRO Nepal Journal Journal of Water, Energy and Environment Issue: 17, July 2015